Analisis Asupan Gula, Garam dan Lemak (GGL) dari Jajanan pada Anak Sekolah Dasar Negeri dan Swasta di Kota Surabaya - Nawang Ferry Risky Mega Puspita; Adriyanto Adriyanto (Universitas Airlangga, Kampus C, Mulyorejo, Surabaya-60115, East Java, Indonesia, 2019)
Background: School age children frequently buy snacks that near them, even thought snacks available in school contain an average amount of sugar, salt and fat. Objectives: The purpose of this study was to analyze intake of sugar, salt and fat from public and private elementary school children. Methods: This research was cross sectional design. The samples were 131 children in IV dan V class public and private elementary school, taken by proportional random sampling method and simple random sampling. Data were collected by interview method used Semi Quantitative Food Frequency questionare. Data were analysed by Mann Whitney. Results: Different test of intake sugar, salt and fat in both school were intake sugar (p=0.001), intake salt (0.000) and intake fat (0.000). Contributed intake of sugar, salt and fat from snacks in public school were 130.6%, 86% and 65.7% from standart per day, even thought contributed intake of sugar, salt and fat from snacks in private school were 81.2%, 44% and 35.8% from standart per day.Conclusions: The conclusion of this study showed that there was had difference intake of sugar, salt and fat between children in public and private school. Intake of sugar, salt and fat in public school more higher than private school signed with intake of sugar, salt and fat more than 50% from standart consumtion per day. Intake of sugar, salt and fat moreover standart in long periode does change nutritional status, so to prohibition obesity in children must limit consumtion snacks especially sweets, salty and fatty. Beside that, children must have education about healthy snacks.ABSTRAKLatar Belakang: Anak sekolah cenderung membeli jajanan yang dekat dengan mereka, sedangkan makanan jajanan yang tersedia di sekolah rata-rata mengandung gula, garam dan lemak dalam jumlah yang tinggi.Tujuan: Penelitian ini bertujuan menganalisis asupan gula, garam dan lemak dari jajanan pada anak sekolah dasar negeri dan swasta.Metode: Desain ini adalah cross sectional. Sampel penelitian sebanyak 131 siswa kelas IV dan V di SD negeri dan swasta yang dipilih dengan proportional random sampling lalu dilanjutkan dengan simple random sampling. Pengumpulan data meliputi wawacara menggunakan form Semi Quantitative Food Frequency. Analisis data dilakukan dengan uji Mann Whitney.Hasil: Uji beda untuk asupan GGL di sekolah dasar negeri dan swasta yaitu asupan gula (p = 0,001), asupan garam (p=0,000) dan asupan lemak (p=0,000). Kontribusi asupan GGL dari jajanan di SD negeri berturut-turut sebesar 130,6%, 86% dan 65,7% dari batas konsumsi GGL sehari, sedangkan asupan GGL dari jajanan di SD swasta berkontribusi berturut-turut sebesar 81,2%, 44% dan 35,8% dari batas konsumsi GGL sehari. Kesimpulan: Ada perbedaan asupan GGL dari anak yang bersekolah di SD negeri dan SD swasta. Asupan GGL lebih tinggi pada anak yang bersekolah di SD negeri dibandingkan di SD swasta ditandai dengan konsumsi GGL yang melebihi 50% dari batas konsumsi GGL sehari. Asupan GGL yang berlebihan dalam jangka waktu yang relatif lama dapat menyebabkan perubahan status gizi sehingga, asupan GGL tetap perlu dijaga agar tidak melebihi batas konsumsinya dengan cara membatasi jajanan yang manis, gurih dan berlemak serta memberikan pendidikan gizi tentang jajanan sehat bagi anak.